Government House - (:unkn) unknown (The Bonanza, Smith Bros and Co., Port of Spain, Trinidad, 2009)
A painting of the governor's residence with two women and two children standing at the fountain in the Botanic Gardens which is at the front of the dwelling. Behind this residence are the green hills of St. Ann's. Postcard number B 2225.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; Botanical gardens--Trinidad and Tobago; Fountains--Trinidad and Tobago; Architecture--Trinidad and Tobago; Gardens--Trinidad and Tobago; Garden ornaments and furniture--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; President's House, The